Obesity, Inflammation and Cancer - Dannenberg, Andrew J.; Berger, Nathan A. (Energy Balance and Cancer, 2013)
In addition to their metabolic and endocrinologic effects, obesity and adipose tissue have now been shown to be associated with chronic low grade inflammation resulting in cellular and humoral factors of which the latter may act by endocrine, paracrine and autocrine mechanisms. These inflammatory mediators have increasingly been suggested as contributing to the obesity link to carcinogenesis and cancer promotion. Obesity, Inflammation and Cancer focuses on recent developments and cutting edge research pointing to inflammation and inflammatory factors as key mediators of this linkage. It also describes possible strategies for targeting inflammation as an approach to cancer prevention and control. Students, researchers and clinicians, especially those interested in the relation of obesity to cancer and the role of inflammation and its impact on cancer, will find this volume particularly useful. It provides important insight on the role of inflammation in cancer etiology and progression and serve as a platform for developing future research in this area.